The importance of teacher support: Differential impacts by gender and sexuality. (21st February 2017) - Dessel, Adrienne B.; Kulick, Alex; Wernick, Laura J.; Sullivan, Daniel
ABSTRACT: Teachers play an important role in shaping the experiences of high school students with regard to patterns of heteronormativity and binary gender norms, particularly for lesbian, gay, bisexual, transgender, and questioning (LGBTQ) students. A climate survey of high school students ( n = 953) in the United States examined the association between students' well‐being and their relationships with teachers. The sample was majority white (65.8%) and multiracial (14.1%). Cisgender (cis)‐girls (49.6%), cis‐boys (41.2%), and trans students (9.2%), as well as heterosexual (78.4%) and LGBQ students (21.6%) were represented. Regression models indicate teachers' use of oppressive language and their intervention in situations of bias and students' trust and comfort with teachers were significantly associated with students' self‐esteem. Teachers' use of biased language was directly associated with student self‐reported grades. Moderation tests indicate teacher relationships are strongly associated with heterosexual and cisgender students' wellbeing. Recommendations for teacher education and future research are discussed.